A flowable composite resin, its preparation method and use

CN117736531BActive Publication Date: 2026-10-20GUILIN KEVIN PETER TECHNOLOGY CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202311761160.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-20
Publication Date
2026-10-20
Estimated Expiration
2043-12-20

AI Technical Summary

Technical Problem

这种组合物会伴随着粘性发生不受控的变化,其赋形性和流动性方面还存在改善的余地

Benefits of technology

[0037]本发明提供的流动复合树脂具有超低流动的特性,从注射器前端针头吐出后具有稳定不变的形态,在临床上特别适用于构筑结构,如做侧壁、假壁、做龈壁提升和牙尖嵴等牙齿修复材料,且得到的构筑结构的力学性能较优。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure QLYQS_1
    Figure QLYQS_1
  • Figure QLYQS_2
    Figure QLYQS_2
  • Figure BDA0004618599630000021
    Figure BDA0004618599630000021
Patent Text Reader

Abstract

The present application relates to the technical field of resin material, and more particularly to a flowable composite resin, a preparation method and application thereof.The flowable composite resin comprises: 25wt%-50wt% of polymer resin monomer; 50wt%-75wt% of inorganic filler; 0.01wt%-3wt% of rheological modifier; and 0.01wt%-3wt% of additive, wherein the sum of the amount of the components is 100%; the rheological modifier comprises at least one of a first rheological modifier and a second rheological modifier; the first rheological modifier has a structure shown in formula I; and the second rheological modifier has a structure shown in formula II.The flowable composite resin has the characteristics of super-low flow, and has a stable form after being discharged from the front needle of the injector, and is particularly suitable for constructing structures, such as making side walls, false walls, gum wall lifting and tooth tip ridge, and the like, in the clinic, and the mechanical properties of the constructed structures are relatively optimal.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of resin materials technology, and in particular to a flowable composite resin, its preparation method and application. Background Technology

[0002] Flowable composite resin, also known as flowable resin, was introduced in 1995 and has since experienced rapid development and widespread application. Flowable composite resin is used for treatment by directly filling dental cavities with a paste through a needle attached to the front end of a container holding the paste, and having an orifice smaller than the cavity diameter. Therefore, the filling operation can be completed simply by flowing the paste into the cavity from a syringe, shortening the treatment time and offering significant convenience in clinical practice.

[0003] For flowable composite resins, a high filler content is advantageous to achieve excellent mechanical properties while reducing polymerization shrinkage during curing. However, for the medical treatment of tooth defects, not only are the material properties of the flowable composite resin crucial, but the pretreatment performed by the user before polymerization is also essential. When the flowable composite resin is extruded from the needle and filled into the cavity, the morphological characteristics of the paste extruded significantly affect the ease of cavity treatment. For example, when the extruded paste has a certain degree of fluidity, its shape-forming properties are insufficient to construct structures, which is not conducive to the clinical creation of lateral walls, pseudo-walls, gingival wall elevations, and cusp ridges for cavity treatment. However, according to current technology, simply adjusting the filler ratio to modify the flowability and consistency of the flowable composite resin will result in uncontrolled changes in viscosity. For example, patent CN 104797232 B mentions preparing a dental flowable composite resin suitable for use as a dental application by combining inorganic fillers and polymerizable monomers of different particle sizes and adjusting their ratio. This composition is accompanied by uncontrolled changes in viscosity, and there is room for improvement in its shape and flow properties. Summary of the Invention

[0004] In view of this, the technical problem to be solved by the present invention is to provide a flowable composite resin, its preparation method and application. The flowable composite resin provided by the present invention has the characteristics of ultra-low flow and has a stable and unchanged shape after being ejected from the needle tip of the syringe. It is particularly suitable for constructing structures in clinical practice, such as lateral walls, pseudo-walls, gingival wall lifting and cusp ridges, etc.

[0005] This invention provides a flowable composite resin, comprising:

[0006]

[0007] The sum of the amounts of the components is 100%;

[0008] The rheology modifier includes at least one of a first rheology modifier and a second rheology modifier;

[0009] The first rheology modifier has the structure shown in Formula I:

[0010] R 1 -OOC-HN-R 3 -NH-COO-R 2 Formula I;

[0011] In Equation I, R 1 and R 2 Independently selected from long-chain aliphatic hydrocarbon groups or long-chain hyperbranched polymer groups; R 3 It consists of groups with polyethylene glycol segments, and the number average molecular weight is between 2000 and 20000;

[0012] The second rheology modifier has the structure shown in Formula II:

[0013] R 4 -HN-CO-NH-R 5 Formula II;

[0014] In formula II, R 4 It is a hydrocarbon chain containing an organic amine group; R 5 It is an aromatic group or a long-chain hyperbranched polymer group with an isocyanate group.

[0015] Preferably, the polymeric resin monomer includes a main monomer and an active diluent monomer;

[0016] The main monomer includes at least one of bisphenol A-dimethacrylate, ethoxylated bisphenol A dimethacrylate, and dimethacrylate formate.

[0017] The reactive diluent monomer includes at least one of triethylene glycol dimethacrylate, trimethylolpropane tri(meth)acrylate, trimethylolpropane tri(meth)acrylate, polyethylene glycol (400) dimethacrylate, 1,12-dodecanediol dimethacrylate, and 1,6-hexanediol diacrylate.

[0018] Preferably, the mass ratio of the main monomer to the reactive diluent monomer is 2 to 10:1.

[0019] Preferably, the inorganic filler includes inorganic particulate filler a and inorganic ultrafine filler b;

[0020] The inorganic particulate filler a is obtained by surface treatment of the first filler with a first silane coupling agent;

[0021] The first filler includes at least one of barium glass powder, alumina glass powder, strontium glass powder, composite oxide particles, ceramics, zirconium oxide, and ytterbium fluoride;

[0022] The first silane coupling agent includes at least one of KH550, KH570 and KH563;

[0023] The inorganic ultrafine filler b is obtained by surface treatment of the second filler with a second silane coupling agent;

[0024] The second filler includes at least one of fumed silica, hydroxyapatite, and ytterbium fluoride;

[0025] The second silane coupling agent includes at least one of KH550, KH570 and KH563.

[0026] Preferably, the average particle size of the inorganic particulate filler a is 0.1–1.0 μm;

[0027] The average particle size of the inorganic particulate filler b is 10–90 nm.

[0028] Preferably, in the inorganic filler, the mass ratio of inorganic particulate filler a to inorganic ultrafine filler b is 15-200:1.

[0029] Preferably, the additive includes at least one of titanium dioxide, iron oxide pigment, photoinitiator, anti-aging agent, polymerization inhibitor and photoinitiation accelerator.

[0030] Preferably, the photoinitiator includes at least one selected from camphorquinone, 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, 1-hydroxycyclohexylbenzophenone, and benzophenone;

[0031] The anti-aging agent includes at least one of 2-hydroxy-4-methoxybenzophenone, benzotriazole and UV-9;

[0032] The polymerization inhibitor includes at least one of 4-methoxyphenol, phenol, and hydroquinone;

[0033] The photoinitiator includes ethyl p-N,N-dimethylaminobenzoate and / or methacrylamide.

[0034] The present invention also provides a method for preparing the above-described flowable composite resin, comprising the following steps:

[0035] Under light-protected conditions, the polymer resin monomers, rheology modifiers, and additives are heated and mixed, then mixed with inorganic fillers, and degassed under vacuum to obtain a flowable composite resin.

[0036] The present invention also provides an application of the flowable composite resin described above, or the flowable composite resin prepared by the preparation method described above, as a dental restorative material.

[0037] The flowable composite resin provided by this invention has ultra-low flow characteristics and maintains a stable shape after being ejected from the needle tip of the syringe. It is particularly suitable for constructing structures in clinical practice, such as lateral walls, pseudo-walls, gingival wall lifting, and cusp ridges, and the resulting constructed structures have superior mechanical properties. Attached Figure Description

[0038] Figure 1 This is an appearance diagram of the flowable composite resin of Embodiment 1 of the present invention. Detailed Implementation

[0039] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0040] This invention provides a flowable composite resin, comprising:

[0041]

[0042] The sum of the amounts of the components is 100%.

[0043] In some embodiments of the present invention, the polymeric resin monomer includes a main monomer and an active diluent monomer;

[0044] The main monomer includes at least one of bisphenol A-dimethacrylate, ethoxylated bisphenol A dimethacrylate, and dimethacrylate formate.

[0045] The reactive diluent monomer includes at least one of triethylene glycol dimethacrylate, trimethylolpropane tri(meth)acrylate, trimethylolpropane tri(meth)acrylate, polyethylene glycol (400) dimethacrylate, 1,12-dodecanediol dimethacrylate, and 1,6-hexanediol diacrylate.

[0046] In some embodiments of the present invention, the mass ratio of the main monomer to the reactive diluent monomer is 2 to 10:1.

[0047] In some embodiments of the present invention, the content of polymeric resin monomer in the flowing composite resin is 35 wt%.

[0048] In some embodiments of the present invention, the inorganic filler includes inorganic particulate filler a and inorganic ultrafine filler b.

[0049] The inorganic particulate filler a is obtained by surface treatment of the first filler with a first silane coupling agent.

[0050] The average particle size of the inorganic particulate filler a is 0.1 to 1.0 μm.

[0051] The first filler includes at least one of barium glass powder, aluminum glass powder, strontium glass powder, composite oxide particles, ceramics, zirconium oxide, and ytterbium fluoride.

[0052] The first silane coupling agent includes at least one of KH550, KH570 and KH563.

[0053] In some embodiments of the present invention, the method for preparing the inorganic particulate filler a includes the following steps:

[0054] The hydrolyzed first silane solution was added dropwise to the first filler slurry under stirring, heated to 100-150℃, stirred and reacted, and then dried to obtain inorganic particulate filler a;

[0055] The preparation method of the first filler slurry includes the following steps:

[0056] The first filler was mixed with anhydrous ethanol solution and ultrasonically treated to obtain the first filler slurry.

[0057] The method for preparing the hydrolyzed first silane solution includes the following steps:

[0058] After adjusting the pH of the alcohol solution to 3.0–4.0 with glacial acetic acid, it is mixed with the first silane coupling agent and subjected to a pre-hydrolysis reaction at 100–150°C to obtain the hydrolyzed first silane solution.

[0059] In the preparation of the first filler slurry:

[0060] The anhydrous ethanol solution has a mass concentration of 99%.

[0061] The mass ratio of the first filler to the anhydrous ethanol solution is 45-55:15-25, for example, 50:20;

[0062] The ultrasonic treatment time is 10 to 30 minutes.

[0063] In the preparation of the first silane solution after hydrolysis:

[0064] The alcohol solution is an ethanol solution, which can be obtained by mixing anhydrous ethanol and water. The mass concentration of the alcohol solution is 50%.

[0065] The mass ratio of the alcohol solution to the first silane coupling agent is 7-9:1-3, for example 8:2.

[0066] The mass ratio of the first silane coupling agent to the first filler is 2 to 10:100, for example, 10:100.

[0067] The pre-hydrolysis reaction is carried out under stirring conditions. The stirring is magnetic stirring. The pre-hydrolysis reaction time is 30–60 min.

[0068] After obtaining the first filler slurry and the hydrolyzed first silane solution, the hydrolyzed first silane solution is added dropwise to the first filler slurry under stirring. The mixture is heated to 100-150°C, stirred and reacted, and then dried to obtain inorganic particulate filler a.

[0069] The stirring reaction takes 2 to 6 hours. The stirring is performed using magnetic stirring.

[0070] The drying process is vacuum drying, with a drying temperature of 100–150°C and a drying time of 10–15 hours.

[0071] The inorganic ultrafine filler b is obtained by surface treatment of the second filler with a second silane coupling agent.

[0072] The average particle size of the inorganic particulate filler b is 10-90 nm, for example, 15 nm.

[0073] The second filler includes at least one of fumed silica, hydroxyapatite, and ytterbium fluoride.

[0074] The second silane coupling agent includes at least one of KH550, KH570 and KH563.

[0075] In some embodiments of the present invention, the preparation method of the inorganic ultrafine filler b includes the following steps:

[0076] The hydrolyzed second silane solution was added dropwise to the second filler slurry under stirring, heated to 100-150℃, stirred and reacted, and then dried to obtain inorganic particulate filler a;

[0077] The preparation method of the second filler slurry includes the following steps:

[0078] The second filler was mixed with anhydrous ethanol solution and ultrasonically treated to obtain a slurry of the second filler.

[0079] The method for preparing the hydrolyzed second silane solution includes the following steps:

[0080] After adjusting the pH of the alcohol solution to 3.0–4.0 with glacial acetic acid, it is mixed with the second silane coupling agent and subjected to a pre-hydrolysis reaction at 100–150 °C to obtain the hydrolyzed second silane solution.

[0081] In the preparation of the second filler slurry:

[0082] The anhydrous ethanol solution has a mass concentration of 99%.

[0083] The mass ratio of the second filler to the anhydrous ethanol solution is 45-55:15-25, for example, 50:20;

[0084] The ultrasonic treatment time is 10 to 30 minutes, for example, 15 minutes.

[0085] In the preparation of the hydrolyzed second silane solution:

[0086] The alcohol solution is an ethanol solution, which can be obtained by mixing anhydrous ethanol and water. The mass concentration of the alcohol solution is 50%.

[0087] The mass ratio of the alcohol solution to the second silane coupling agent is 7-9:1-3, for example 8:2.

[0088] The mass ratio of the second silane coupling agent to the second filler is 2 to 10:100, for example, 10:100.

[0089] The pre-hydrolysis reaction is carried out under stirring conditions. The stirring is magnetic stirring. The temperature of the pre-hydrolysis reaction is 120°C; the time is 30–60 min, for example, 45 min.

[0090] After obtaining the second filler slurry and the hydrolyzed second silane solution, the hydrolyzed second silane solution is added dropwise to the second filler slurry under stirring. The mixture is heated to 100-150°C, stirred and reacted, and then dried to obtain inorganic particulate filler a.

[0091] The stirring reaction is carried out at a temperature of 120°C for 2–6 hours, for example, 4 hours. The stirring is performed using magnetic stirring.

[0092] The drying process is vacuum drying, with a drying temperature of 100–150°C, such as 130°C, and a drying time of 10–15 hours, such as 12 hours.

[0093] In some embodiments of the present invention, the mass ratio of inorganic particulate filler a to inorganic ultrafine filler b in the inorganic filler is 15 to 200:1.

[0094] In some embodiments of the present invention, the content of inorganic filler in the flowing composite resin is 62.5 wt%, 63 wt%, or 63.5 wt%.

[0095] In some embodiments of the present invention, the rheology modifier includes at least one of a first rheology modifier and a second rheology modifier.

[0096] The first rheology modifier has the structure shown in Formula I:

[0097] R 1 -OOC-HN-R 3 -NH-COO-R 2 Formula I;

[0098] In Equation I, R 1 and R 2 Independently selected from long-chain aliphatic hydrocarbon groups or long-chain hyperbranched polymer groups; R 3 It consists of groups with polyethylene glycol segments, and the number average molecular weight is between 2000 and 20000.

[0099] The second rheology modifier has the structure shown in Formula II:

[0100] R 4 -HN-CO-NH-R 5 Formula II;

[0101] In formula II, R 4 It is a hydrocarbon chain containing an organic amine group; R 5 It is an aromatic group or a long-chain hyperbranched polymer group with an isocyanate group.

[0102] In some embodiments of the present invention, the first rheology modifier has a structure having formula I-1 or formula I-2.

[0103]

[0104] In Equation I-1, R is -(CH2). 50 -

[0105] In some embodiments of the present invention, the second rheology modifier has the structure of formula II-1 or formula II-2;

[0106]

[0107] The present invention does not impose any special restrictions on the source of the first rheology modifier; it can be self-made or commercially available.

[0108] The present invention does not impose any special restrictions on the source of the second rheology modifier; it can be self-made or commercially available.

[0109] In some embodiments of the present invention, the rheology modifier content in the flow composite resin is 0.5 wt%, 1 wt%, or 1.5 wt%.

[0110] In some embodiments of the present invention, the additive includes at least one of titanium dioxide, iron oxide pigment, photoinitiator, anti-aging agent, polymerization inhibitor and photoinitiation accelerator.

[0111] The photoinitiator includes at least one of camphorquinone, 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, 1-hydroxycyclohexylbenzophenone, and benzophenone.

[0112] The anti-aging agent includes at least one of 2-hydroxy-4-methoxybenzophenone, benzotriazole, and UV-9.

[0113] The polymerization inhibitor includes at least one of 4-methoxyphenol, phenol, and hydroquinone.

[0114] The photoinitiator includes ethyl p-N,N-dimethylaminobenzoate and / or methacrylamide.

[0115] In some embodiments of the present invention, the content of additives in the flowable composite resin is 1 wt%.

[0116] In this invention, the rheology modifier can interact with the polymeric resin monomers to form a non-Newtonian fluid. The rheology modifiers interact with each other, as well as with the surfaces of the resin monomers and inorganic fillers, to form a network structure, thereby achieving excellent thixotropic effects. Simultaneously, the temporary network structure formed by this rheology modifier is constantly undergoing a process of destruction and reformation, thus imparting excellent flowability to the flowing resin. Furthermore, the rheology modifier of this invention can also be used in combination with other types of rheology modifiers.

[0117] The present invention also provides a method for preparing the above-described flowable composite resin, comprising the following steps:

[0118] Under light-protected conditions, the polymer resin monomers, rheology modifiers, and additives are heated and mixed, then mixed with inorganic fillers, and degassed under vacuum to obtain a flowable composite resin.

[0119] The raw material components and dosage ratios used in the preparation method of the flowable composite resin are the same as those described above, and will not be repeated here.

[0120] In some embodiments of the present invention, the heating and mixing temperature is 50–70°C, for example, 60°C. The mixing method is stirring.

[0121] In some embodiments of the present invention, degassing under vacuum conditions includes degassing under vacuum stirring.

[0122] The present invention also provides an application of the flowable composite resin described above, or the flowable composite resin prepared by the preparation method described above, as a dental restorative material.

[0123] The flowable composite resin provided by this invention has ultra-low flow characteristics and maintains a stable and unchanging shape after being ejected from the syringe needle. Clinically, it is particularly suitable for constructing structures, such as lateral walls, pseudo-walls, gingival wall lifts, and cusp ridges, etc., as dental restorative materials. Therefore, this invention seeks protection for the application of the described flowable composite resin as a dental restorative material.

[0124] The present invention does not impose any special restrictions on the source of the raw materials used above, and they can be commercially available.

[0125] To further illustrate the present invention, the following detailed description of a flowable composite resin, its preparation method, and its application, in conjunction with embodiments, is provided by the present invention, but should not be construed as limiting the scope of protection of the present invention.

[0126] In the examples, the rheology modifier ALF (Formula I-1) was prepared as follows:

[0127] Weigh 50g of polyethylene glycol (number average molecular weight 5000), then add it to a three-necked flask equipped with a thermometer and rubber stopper. Dehydrate the flask under vacuum at 120℃ and 0.03MPa for 2 hours. Cool the dehydrated PEG to 60℃ and attach a stirring rod to a stirrer. Weigh 20g of isophorone diisocyanate using an electronic balance and add it to the three-necked flask containing the PEG. Add 0.3% (by mass) of dibutyltin dilaurate catalyst relative to the total reactants. React at 60℃ for 6 hours. When the viscosity of the reaction system in the three-necked flask reaches 10000 cps, add 5g of acetone to reduce the viscosity and ensure a complete reaction. Then, add 20g of glyceryl monostearate and 20g of cetyl alcohol. React at 60℃ for 6 hours. When the viscosity of the reaction system in the three-necked flask reaches 10000 cps, add 5g of cetyl alcohol to reduce the viscosity and ensure a complete reaction. Finally, the product obtained from the reaction was cooled: 15g of a 50% ethanol aqueous solution was weighed and added to the polymer in three portions of 5g each, while stirring continuously. The completely emulsified emulsion was then poured into a container and sealed to obtain the rheology modifier ALF. The reaction equation is shown below:

[0128]

[0129] Where R is -(CH2) 50 -

[0130] Preparation of rheology modifier BLF (Formula II-2):

[0131] 50g of octadecylamine and 100g of toluene solvent were mixed in a reaction vessel and heated to 50℃. Under uniform stirring, 10g of a 20% toluene 2,6-diisocyanate solution was added dropwise to the vessel to react with the octadecylamine for 20 min. 5g of water was added to remove unreacted isocyanate. The sample was then filtered and dried to obtain the rheology modifier BLF. The reaction equation is shown below:

[0132]

[0133] Abbreviations for materials used in the examples and comparative examples:

[0134]

[0135] Preparation of inorganic ultrafine filler b (the above-mentioned SiO2-15):

[0136] (1) Weigh 50g of the second filler (fumed silica) and add it to 20g of anhydrous ethanol solution (mass concentration of 99%) to prepare the second filler slurry, and then sonicate it for 15min.

[0137] (2) Prepare an ethanol solution with a mass concentration of 50% by mixing anhydrous ethanol and water, add glacial acetic acid to adjust the pH of the solution to 3.0-4.0, and then add 5g of the second silane coupling agent (KH570); wherein the mass ratio of the ethanol solution to the second silane coupling agent is 8:2, and the mass ratio of the second silane coupling agent to the second filler is 10:100. Perform a pre-hydrolysis reaction by magnetic stirring at 120℃ for 45min to obtain the hydrolyzed second silane solution;

[0138] (3) The hydrolyzed second silane solution was added dropwise to the second filler slurry under stirring, heated to 120°C, magnetically stirred for 4 hours, and then vacuum dried at 130°C for 12 hours to obtain SiO2-15.

[0139] Preparation of inorganic particulate filler a (GDB-0.2 above):

[0140] (1) Weigh 50g of the first filler (barium glass powder, aluminum glass powder and strontium glass powder; particle size ≤0.2μm) and add it to 20g of anhydrous ethanol solution (mass concentration of 99%) to prepare the first filler slurry, and then sonicate it for 15min.

[0141] (2) Prepare an ethanol solution with a mass concentration of 50% by mixing anhydrous ethanol and water, add glacial acetic acid to adjust the pH of the solution to 3.0-4.0, and then add 5g of the first silane coupling agent (KH550); wherein the mass ratio of ethanol solution to first silane coupling agent is 8:2, and the mass ratio of first silane coupling agent to first filler is 10:100. Perform a pre-hydrolysis reaction by magnetic stirring at 120℃ for 45min to obtain the hydrolyzed first silane solution;

[0142] (3) The first silane solution after hydrolysis was added dropwise to the first filler slurry under stirring, and heated to 120°C and magnetically stirred for 4 hours. Then it was vacuum dried at 130°C for 12 hours to obtain GDB-0.2.

[0143] Preparation of inorganic particulate filler a (GDB-0.4 above):

[0144] The difference between the preparation method of GDB-0.2 and that of GDB-0.2 is that the particle size of barium glass powder, aluminum glass powder and strontium glass powder in the first filler is ≤0.4μm.

[0145] Preparation of inorganic particulate filler a (GDB-0.7 above):

[0146] The difference between the preparation method of GDB-0.2 and that of GDB-0.2 is that the particle size of barium glass powder, aluminum glass powder and strontium glass powder in the first filler is ≤0.7μm.

[0147] Examples 1-5 and Comparative Examples 1-5

[0148] Preparation of flowable composite resin:

[0149] Under light-protected conditions, the polymer resin monomer, rheology modifier, and additives are heated to 60°C and mixed, then mixed with inorganic fillers, and degassed under vacuum stirring to obtain a flowable composite resin.

[0150] The raw material components and dosage ratios used in the preparation of the flowable composite resin are shown in Table 1. The performance of the flowable composite resin was tested, and the results are shown in Table 1.

[0151] Flexural strength test: Following the ISO 4049:2009 test standard, samples were prepared by injecting them into a 2mm × 2mm × 25mm metal mold. Polyester films were used to cover the surface and bottom of the specimens to prevent matrix leakage and the presence of an anaerobic layer. The specimens were cured using a Woodpecker O-star UV curing machine in standard mode, with five overlapping irradiations from left to right, each irradiated for 20 seconds to ensure complete curing. The specimens were then stored in distilled water at 37℃ for 24 hours in the dark. Three-point bending strength and modulus of elasticity were tested using a universal testing machine. The specimens were loaded at a rate of 0.75mm / min until fracture, and the maximum load and slope applied at the fracture point were recorded. Finally, the flexural strength and modulus of elasticity were calculated according to the formulas in the ISO 4049:2009 test standard.

[0152] Surface hardness test: A circular specimen was prepared by injecting the sample into a metal mold with a diameter of 6 mm and a height of 2 mm. The surface of the specimen was then exposed to UV light for 20 seconds using a Woodpecker O-star UV curing machine in standard mode. The specimen was then stored in distilled water at 37℃ in the dark for 24 hours. The surface hardness of the material was tested using a Vickers hardness tester with a loading force of 980 mN for 10 seconds. The digital hardness value was recorded directly, and the test was repeated three times, with the average value taken.

[0153] Compressive strength: Samples were injected into a metal mold with a diameter of 4 mm and a height of 6 mm to prepare specimens. The surface and bottom of the specimens were irradiated for 20 seconds each using a Woodpecker O-star UV curing machine in standard mode to ensure complete curing (n=5). The specimens were stored in distilled water at 37℃, protected from light, for 24 hours. A universal testing machine was used for compressive strength testing at a loading speed of 1 mm / min until the specimen fractured. The maximum load during fracture was recorded, and the compressive strength (CS) was calculated using the following formula:

[0154] CS=4F / πd 2

[0155] Where F is the maximum load at the fracture point, and d is the diameter of the specimen.

[0156] X-ray resistance: The samples were tested for X-ray resistance according to test method 7.14 in YY1042—2011 Dental Polymer-based Restorative Materials.

[0157] Extrusion force: The extrusion force was measured using a syringe made of polyacrylic acid resin (8 mm inner diameter × 63 mm length), a container consisting of a cylindrical plunger inserted into the syringe from the rear end, and a needle tip (0.65 mm inner diameter × 19 mm length, with the needle tip bent at 45 degrees 8.5 mm from the front end) fitted to the front end of the aforementioned syringe. The container was constructed of a component that is opaque to ambient light.

[0158] Shape properties: A 4mm diameter circle was pre-drawn on a 30mm × 30mm square glass plate. Using the same container and needle tip used in the above-mentioned ejection power evaluation, 0.035-0.037g of paste was ejected from this circle. The glass plate was placed horizontally in a thermostat at 37°C and left to stand for 30 seconds. The shape of the paste was visually observed, and the shape (shape properties) of the ejected material was evaluated according to the following evaluation criteria. It should be noted that shape properties are rated from 1 to 5, representing the best to the worst.

[0159] 1: It did not form a hemispherical shape and maintained the shape of the extruded material.

[0160] 2: Forms a hemispherical shape, slightly retaining the shape of the extruded material.

[0161] 3: Form a hemisphere and maintain this shape.

[0162] 4: Forms a hemisphere, but with a slightly lower height.

[0163] 5: It fails to form a hemisphere, or even if it does, it collapses immediately.

[0164] Operability: A 10mm inner diameter and 2mm thickness acrylic resin ring was filled with flowing composite resin, and a 5mm diameter plastic cylindrical rod was submerged 1mm into its center. The cylindrical rod was pulled up using a universal testing machine AG-IS (Shimadzu Corporation) at a speed of 50mm / min, and the distance of resin separation was measured and taken as the string length. It should be noted that a string length greater than 40mm is considered unacceptable, 30-40mm is acceptable, 20-30mm is good, and less than 20mm is excellent.

[0165] Table 1. Raw material components and dosage ratios used in the preparation of the flowable composite resins of Examples 1-5 and Comparative Examples 1-5.

[0166]

[0167]

[0168] Table 1 (Continued from Table 1)

[0169]

[0170] Examples 1-5 show that the flowable composite resins with added rheology modifiers ALF and BLF of the present invention, when added at suitable amounts, exhibit excellent shapeability, workability, and suitable extrusion power, as shown in Examples 3-5. Comparative Example 6 shows that adding polyamide wax rheology modifier also promotes the shapeability, workability, and extrusion power of the flowable composite resin to some extent, but the effect is not as good as in Examples 1-5.

[0171] Examples 3-5 all exhibited good shape retention, failing to form hemispherical shapes and maintaining the extruded shape. In contrast, Comparative Example 1, without any rheology modifier, showed poor shape retention, either failing to form hemispherical shapes or collapsing immediately if hemispherical shapes were formed. Although Comparative Examples 4-5, after adding SiO2-15 and CMC respectively, also showed good shape retention, failing to form hemispherical shapes and maintaining the extruded shape, their ejection forces were all greater than 50 N, and their fiber lengths were only 30-40 mm (i.e., only passable operability). In contrast, Examples 3-5 all had ejection forces less than 20 N, similar to Comparative Example 1, and fiber lengths less than 20 mm, demonstrating excellent operability. Therefore, the flowable composite resin of this invention, with the addition of rheology modifiers ALF and BLF, can take into account the excellent properties of shapeability, operability and suitable ejection force, that is, it has the characteristics of ultra-low flow and has a stable and unchanged shape after being ejected from the needle tip of the syringe. It is particularly suitable for constructing structures in clinical practice, such as lateral walls, pseudo-walls, gingival wall elevation and cusp ridges.

[0172] Furthermore, compared to Comparative Example 1, Examples 1-5, which added rheology modifiers ALF and BLF, did not show significant changes in flexural strength, surface hardness, compressive strength, and X-ray spectroscopy resistance, indicating that the appropriate addition of rheology modifiers ALF and BLF does not adversely affect the mechanical properties of the flowable composite resin. However, Comparative Example 6, which added polyamide wax, showed varying degrees of decrease in its mechanical properties (such as flexural strength, surface hardness, and compressive strength), indicating that polyamide wax has an adverse effect on the mechanical properties of the resin, presumably acting as a plasticizer. The flowable composite resin of this invention exhibits mechanical properties far exceeding industry standards, possessing advantages such as excellent mechanical strength and high X-ray spectroscopy resistance.

[0173] Figure 1 This is an appearance diagram of the flowing composite resin of Embodiment 1 of the present invention. From... Figure 1 As can be seen, the leftmost diagram shows the shaping properties of Example 3, where a hemisphere is not formed and the extruded shape remains unchanged. The middle diagram shows the shaping properties of Comparative Example 6, where a hemisphere is formed and the shape is maintained. The rightmost diagram shows the shaping properties of Comparative Example 1, where a hemisphere is not formed, or even if a hemisphere is formed, it collapses immediately.

[0174] The above description of the disclosed embodiments enables those skilled in the art to make or use the invention. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the invention. Therefore, the invention is not to be limited to the embodiments shown herein, but is to be accorded the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A flowable composite resin, comprising: Polymerized resin monomer 25 wt%~50 wt%; Inorganic fillers 50 wt%~75 wt%; Rheology modifier 0.01 wt%~3 wt%; Additives 0.01 wt%~3 wt%; The sum of the amounts of the components is 100%; The polymer resin monomer includes a main monomer and an active diluent monomer; The main monomer includes at least one of bisphenol A-dimethacrylate, ethoxylated bisphenol A dimethacrylate, and carbamate dimethacrylate. The mass ratio of the main monomer to the reactive diluent monomer is 2~10:1; The rheology modifier is a second rheology modifier; The second rheology modifier has the structure of formula II-1 or formula II-2: Formula II-1; Formula II-2.

2. The flowable composite resin according to claim 1, characterized in that, The reactive diluent monomer includes at least one of triethylene glycol dimethacrylate, trimethylolethane tri(meth)acrylate, polyethylene glycol 400 dimethacrylate, 1,12-dodecanediol dimethacrylate, and 1,6-hexanediol diacrylate.

3. The flowable composite resin according to claim 1, characterized in that, The inorganic filler includes inorganic particulate filler a and inorganic ultrafine filler b; The inorganic particulate filler a is obtained by surface treatment of the first filler with a first silane coupling agent; The first filler includes at least one of barium glass powder, alumina glass powder, strontium glass powder, zirconium oxide, and ytterbium fluoride; The first silane coupling agent includes at least one of KH550, KH570 and KH563; The inorganic ultrafine filler b is obtained by surface treatment of the second filler with a second silane coupling agent; The second filler includes at least one of fumed silica, hydroxyapatite, and ytterbium fluoride; The second silane coupling agent includes at least one of KH550, KH570 and KH563.

4. The flowable composite resin according to claim 3, characterized in that, The average particle size of the inorganic particulate filler a is 0.1~1.0 μm; The average particle size of the inorganic ultrafine filler b is 10~90 nm.

5. The flowable composite resin according to claim 1, characterized in that, In the inorganic packing material, the mass ratio of inorganic particulate packing a to inorganic ultrafine packing b is 15~200:

1.

6. The flowable composite resin according to claim 1, characterized in that, The additives include at least one of titanium dioxide, iron oxide pigments, photoinitiators, anti-aging agents, polymerization inhibitors, and photoinitiation promoters.

7. The flowable composite resin according to claim 6, characterized in that, The photoinitiator includes at least one of camphorquinone, 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, 1-hydroxycyclohexylbenzophenone, and benzophenone; The anti-aging agent includes at least one of 2-hydroxy-4-methoxybenzophenone, benzotriazole and UV-9; The polymerization inhibitor includes at least one of 4-methoxyphenol, phenol, and hydroquinone; The photoinitiator includes ethyl p-N,N-dimethylaminobenzoate.

8. A method for preparing the flowable composite resin according to any one of claims 1 to 7, comprising the following steps: Under light-protected conditions, the polymer resin monomers, rheology modifiers, and additives are heated and mixed, then mixed with inorganic fillers, and degassed under vacuum to obtain a flowable composite resin.

9. The application of the flowable composite resin according to any one of claims 1 to 7, or the flowable composite resin prepared by the preparation method according to claim 8, in the preparation of dental restorative materials.

Citation Information

Patent Citations

  • Dental curing compositions and dental flowable composite resins

    CN104797232B

  • Fluidized bulk filling composite resin without bisphenol A structure as well as preparation and application of flowable bulk filling composite resin

    CN114349903A

  • Dental flowing composite resin with long-term fluorine release property

    CN115778826A